Retrieving Augustine's doctrine of creation : ancient wisdom for current controversy - Ortlund, Gavin, 1983- (Downers Grove IVP Academic, 2020)
"How might premodern exegesis of Genesis inform Christian debates about creation today? Pastor and theologian Gavin Ortlund retrieves Augustine's reading of Genesis 1-3 and considers how his premodern understanding of creation can help Christians today, shedding light on matters such as evolution, animal death, and the historical Adam and Eve"--
Includes bibliographical references and index.
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Bible. -- Criticism, interpretation, etc; Creation. -- History of doctrines -- Early church, ca. 30-600.